Nasal flu vaccine: attitudes and perceptions of parents who use social media - Yasmin Abo Halima; Irene Kiroplis; Olivia Hickey; Peter Hayes; Patrick O’Donnell (James Cook University, 2023)
Background/Aim: In October of 2020, a live attenuated Nasal Flu Vaccine (NFV) was licensed for the first time in Ireland for children aged 2&ndash17 years of age. The uptake of the NFV in Ireland was much lower than expected. The aim of this study was to determine the attitudes of Irish parents towards the NFV, and to examine the relationship between the perceptions of vaccines and the uptake rate.Methods: An 18-question online questionnaire, developed through Qualtrics software®, was distributed via various social media platforms. Data were examined using SPSS to run associations using chi-squared tests. Free text boxes were assessed using thematic analysis.Results: Of the 183 people who participated, 76% of parents had vaccinated their children. 81% of parents would vaccinate all their children, while 65% disagreed with vaccinating only children 5 years or older. The majority of parents agreed that the NFV was safe and effective. Analysis of the text included requests for alternative vaccine locations (22%), difficulties getting an appointment (6%), and a lack of public awareness of the vaccine campaign (19%).Conclusions: Parents are willing to have their children vaccinated but there are barriers to vaccination contributing to the low uptake of the NFV. Increasing the availability of the NFV in pharmacies and schools can increase uptake. Public health messaging around the availability of the NFV is excellent but a more succinct message is needed to highlight the importance of under 5s receiving the vaccine. Future studies should examine the promotion of the NFV by healthcare professionals and general practitioners' attitudes towards the NFV.